PENGEMBANGAN MEDIA KOMIK AUGMENTED REALITY MATERI PECAHAN BERBANTUAN ASSEMBLR EDU KELAS III SDN 2 BENDOGERIT - Isnadatul Hasanah, Nisa; Fatih, Mohamad; Wafa, Khoirul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aimed to develop augmented reality (AR) comic-based learning media for fraction material targeted at 3rd-grade elementary school students. The research method used was research and development (R&D) with the ADDIE model. The results showed that the developed AR comic media was considered feasible and effective in improving students' understanding of fraction concepts. This media could visualize fraction concepts more concretely and attractively, thus encouraging active student engagement. The use of AR technology was proven to help students comprehend the abstract fraction material. Therefore, AR comic media can be an effective alternative for delivering fraction content to 3rd-grade elementary students.   Keywords: augmented reality, comic media, fractions, elementary school